Karakterisasi Batuan pada Daerah Buay Pemaca dan Sekitarnya, Kabupaten OKU Selatan, Sumatera Selatan berdasarkan Observasi Lapangan dan Analisis Petrografi - Afrizya Ade Alya Sandy; Idarwati Idarwati; Muhammad Alfath Salvano Salni (Geosfera: Jurnal Penelitian Geografi, 2026)
Limited integration between petrographic data and interpretations of geological evolution in the Buay Pemaca area and its surroundings has resulted in an incomplete understanding of tectonic controls and regional geological development. This study aims to analyze rock characteristics using a petrographic approach and to examine its implications for the geological history of the study area. The methods employed include macroscopic and microscopic analyses to identify mineral composition, texture, and grain relationships, which are then interpreted within a regional geological framework. The results indicate that the rock variations in the study area record stages of geological evolution controlled by the interaction of magmatic, tectonic, and sedimentary processes. The initial phase is associated with subduction activity that produced volcanic rocks and intrusions, followed by the development of a sedimentary environment transitioning from terrestrial to shallow marine conditions due to transgression and regression mechanisms, and culminating in volcanic activity that again influenced the geological system. This study confirms that rock characteristics are closely related to ongoing regional tectonic dynamics. Thus, the geological evolution of the study area is controlled by repeated interactions between endogenous and exogenous processes that systematically form the rock sequence. The main contribution of this study is the integration of petrographic analysis with a more comprehensive interpretation of geological evolution.